Languages, Fees and the International Scope of Patenting - Dietmar Harhoff; Karin Hoisl; Bruno van Pottelsberghe de la Potterie (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2009)
This paper analyzes firms' choices regarding the geographic scope of patent protection within the European patent system. We develop an econometric model at the patent level to quantify the impact of office fees and translation costs on firms' decision to validate a patent in a particular country once it has been granted by the EPO. These costs have been disregarded in previous studies. The results suggest that both translation costs and fees for validation and renewals have a strong influence on the behavior of applicants. The estimates are then employed to simulate the impact of the London Protocol, a recent policy reform which reduces translation requirements in the European patent system. National validations of patents granted by the EPO are estimated to increase by 29%.
urn:nbn:de:bvb:19-epub-10456-6
Keywords: O30; O31; O38; O57; 650; patents; patent fees; patent validation; renewal fees; translation costs; Internationales Patentrecht; Gebühr; Übersetzung; Variable Kosten; Patent; Europa